Product Concept Design A Review of the Conceptual Design of Products in Industry - Keinonen, Turkka Kalervo.; Keinonen, Turkka Kalervo.; Takala, Roope.; Takala, Roope. (Springer London : Imprint: Springer, 2006)
Globalisation of the world’s economy is leading to rapid change and uncertainties in society, politics and markets. Product design strategies need to respond to these developments. Product Concept Design meets the needs and expectations of academia and practitioners working in design by focussing on the methods for creating products and design strategies in today’s fast-changing business environment. Product Concept Design has been written by a collection of researchers and practising designers from leading companies such as Nokia and Volvo and provides a goldmine of ideas for designers and managers in industry, as well as lecturers in design and design engineering and their students.